Morphological variation in the tropical anole, Anolis casildae (Squamata: Polychrotidae) - Nicholson, Kirsten E; Ibáñez D., Roberto; Jaramillo, César A; Lips, Karen R (Revista de Biología Tropical, 2001)
We describe morphological variation (scalation and coloration) observed among eight individuals of the Panamanian lizard species Anolis casildae. This variation was not observed in the holotype and aids in identification of this recently described species (originally described on the basis of a single, male specimen). This species occurs only in the Reserva Forestal Fortuna (Chiriquí Province) and the adjacent Bosque Protector Palo Seco (Bocas del Toro Province) in western Panama. Anolis casildae can be distinguished from all other Panamanian anole species via six features: (1) two enlarged superciliary scales (the first larger than the second); (2) an anterior nasal scale in contact with the rostral scale or separated from the rostral by one scale; (3) 6–8 sublabial scales to the center of the eye; (4) 3-4 scales between the supraorbital semicircles; (5) unique coloration (4–6 oblique brown bands interspersed by blueoutlined yellow patches; dewlap is a dirty cream color with broad yellow scale rows irregularly interspersed with smaller emerald green scales) and (6) A. casildae occurs from 1 050 to 1 400 m in the Cordillera Central. We also compare our natural history observations of A. casildae to a similar large anole, A. frenatus, a species which we believe A. casildae to be closely related.